The concept of habitus in Pierre Bourdieu: possibility of study in the policy of continuing education of the National Pact for Literacy at the Right Age (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2020)
Based on the concepts of Pierre Bourdieu’s praxiology, this study proposes to present a discussion on the constitution of a habitus in continuous education of literacy teachers, based on the data from the research Continuous Training in National Pact for Literacy at Right Age - PNAIC - and the practice of literacy teachers in the city of Rio Azul – PR (Formação Continuada no Pacto Nacional Pela Alfabetização na Idade Certa – PNAIC – e a prática dos professores alfabetizadores no município de Rio Azul – PR), de Pires (2016), presented to the Stricto Sensu Graduate Program in Education at the Universidade Estadual do Centro Oeste - UNICENTRO. Such discussion took place from the voices and facts that influenced the implementation of PNAIC (context of influence), from the speeches contained in legal documents that materialized this policy (context of text production) and from the speeches of literacy teachers and study advisers of PNAIC (context of practice). Habitus is the generating and unifying principle that translates the intrinsic and relational characteristics of a position in a univocal lifestyle, that is, in a univocal range of choices, goods and practices. From the results, it was verified that the promising speeches of the policy of continuous education of PNAIC and the mention of the literacy teacher as the main and determining character in the literacy process constitute a habitus that meets the internal needs of the political field.Keywords: Continuous education. Habitus. Bourdieu.